A Nano‐Stripe Based Sensor for Temperature Measurement at the Submicrometer and Nano Scales. Issue 19 (30th May 2014) - Huo, Xiaoye; Liu, Haixiao; Liang, Yiran; Fu, Mengqi; Sun, Weiqiang; Chen, Qing; Xu, Shengyong
<x xml:space="preserve">Abstract</x> Submicrometer dual‐stripe temperature sensors made from a single piece of metal thin film (e.g., Pd) are developed. With the narrowest sensor being 900 nm in width, they show sensitivity of 1–2 μV/K for the full range of 10–300 K. The results confirm the size effect in Seebeck coefficient previously observed in microstripe sensors of the same device configuration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>